2020
DOI: 10.3390/app10051626
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Planning with Time-Variant Safety Margin for Autonomous Vehicle Lane Change

Abstract: A lane change is one of the most important driving scenarios for autonomous driving vehicles. This paper proposes a safe and comfort-oriented algorithm for an autonomous vehicle to perform lane changes on a straight and level road. A simplified Gray Prediction Model is designed to estimate the driving status of surrounding vehicles, and time-variant safety margins are employed during the trajectory planning to ensure a safe maneuver. The algorithm is able to adapt its lane changing strategy based on traffic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Wu et al, in their paper, suggest a Gray Prediction Model estimate gaps and find the correct instance of time for lane switching. Continuous path planning is safe and efficient for lane switching [34]. Overtaking is an essential element in motion control because, if not done correctly, it can lead to accidents.…”
Section: Motion Controlmentioning
confidence: 99%
“…Wu et al, in their paper, suggest a Gray Prediction Model estimate gaps and find the correct instance of time for lane switching. Continuous path planning is safe and efficient for lane switching [34]. Overtaking is an essential element in motion control because, if not done correctly, it can lead to accidents.…”
Section: Motion Controlmentioning
confidence: 99%
“…Li et al [ 31 ] proposed risk-aware lane-changing decision making for autonomous vehicles on normal roads. Wu et al [ 32 ] studied the lane-changing decision making of autonomous vehicles on a straight and level road. An et al [ 33 ] explored the lane-changing decision-making process of autonomous vehicles on a straight road under stable steering.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng [12] found that the scholars who studied lane-changing maneuvers mostly focused on lane-changing conditions and believed that is one of the necessary elements for the realization of lane changing. Wu et al [13] employed time-variant safety margins to ensure a safe maneuver during trajectory planning. Most of the studies on lane-changing conditions are based on gap theory, which states that when the critical safety distance meets the requirements, an accident will not occur.…”
Section: Introductionmentioning
confidence: 99%